Analysis of the Responsive Aspects of the Traditional Persian House - Alkhansari, Maryam Gharavi (Journal of Architecture and Urbanism, 2015)
The traditional Persian house is a representative of the culture, way of life, and beliefs of the Persian people during the golden era of Persian civilization in 17th to early 20th centuries. The goal of this paper is to analyze the responsive features of this traditional house in order to provide a more organized recognition of this structure and its fundamental principles. It seems that appreciation of such key principles may help to exit the current confusion in understanding cultural-spatial qualities in contem- porary Iranian housing. In this regard, the paper will introduce the traditional Persian house, and will analyze its different aspects by using the seven criteria of Ian Bentley et al. in the book Responsive Environments (1985). This book speaks of broad, but somewhat universal concepts that can be applied across a wide range of areas such as old environments. This approach can be applied to reconsider the values of traditional environments. The criteria proposed are ‘permeability’, ‘variety’, ‘legibility’, ‘robustness’, ‘visual appropriateness’, ‘richness’ and ‘personalization’. This paper’s analysis will be performed from three main viewpoints: functional-constructional, environmental, and social-cultural. The paper discussions show that the responsiveness criteria are achieved in the traditional Persian house. It seems this achie- vement results from intelligent application of fundamental, structural principles of the traditional Persian house that provides suitable ground for answering functional-constructional, environmental and social-cultural issues through common solutions in an integrated entity.